THE BASICS ON ACCOUNTING PROFESSION SELECTION: LATEST CAPTURE DURING COVID-19 PANDEMIC ERA - Azizah, Nurul; Purnamasari, Fitri (Research In Management and Accounting (RIMA), 2021)
COVID-19 pandemic era is very potential in changing the mindset of students in the accounting field in seeing their future careers. It cannot be denied that there are several factors in how they view the prospects for the accounting profession amid this pandemic. This research was conducted at a university located in Malang City, Indonesia. The data was obtained through interviews with 70 students of the Accounting Department, Faculty of Economics. Interviews were conducted in person for approximately three months in 2020. In connection with the COVID-19 pandemic, interviews were conducted online. It is revealed that financial performance rewards and an ideal work environment are the two main factors that accounting students consider in determining their career path.